Subjects of proof in criminal proceedings on the offences in the economic sphere (Bulletin of Kharkiv National University of Internal Affairs, 2022)
An analysis of scientific approaches and provisions of criminal procedural legislation regarding the determination of the essence, features and structure of evidence in criminal proceedings, including crimes in the economic sphere, has been carried out. It has been determined that evidence in criminal proceedings on crimes in the economic sphere is a structured epistemological and praxeological activity of authorized subjects, which is implemented on the grounds and in the manner prescribed by criminal procedural legislation, and consists in collecting, verifying and evaluating evidence about the circumstances of commiting the named criminal offenses and other circumstances relevant to criminal proceedings. It has been argued that one of the most important elements in the structure of proof is the subjects. The specifics of proof in criminal proceedings on crimes in the field of economy have been clarified. It has been substantiated that the specificity of crimes in the field of economy affects not only the content of the subject of proof, sources of evidence and methods of proof, but also the subjects authorized to carry it out. It has been noted that the subjects of proof in criminal proceedings on crimes in the field of economy should be systematized according to certain criteria, taking into account both criminal procedural and forensic features of this category of criminal offenses and activities for their detection, pre-trial investigation and trial. It has been proposed to single out the following as criteria for the systematization of evidence subjects in the specified criminal proceedings: stages of criminal proceedings; responsibility for pre-trial investigation of crimes in the economic sphere; immediacy of proof. Systematization of subjects of evidence in criminal proceedings on crimes in the field of economy has been carried out.